2001
DOI: 10.1002/1097-4628(20010509)80:6<831::aid-app1161>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structure and properties of conventional and ?high crystallinity? isotactic polypropylenes and their blends with metallocene-catalyzed linear low density polyethylene. II. Morphological studies

Abstract: The morphology of "high crystallinity" polypropylene (h.cr.PP) and metallocene-catalyzed linear low density polyethylene blends has been investigated using optical microscopy, scanning electron microscopy, and wide-angle X-ray scattering. The data obtained were analyzed and compared with results from physical testing. It was concluded that the improved physical performance of pure h.cr.PP, as well as its blends, compared with conventional PP and its blends was due to the alteration (suppression) of spherulitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The change of cutting temperature was required because all samples were too soft and viscous to be cut at room temperature without deformation. The low temperature cutting preserved the sample morphology (17). An Olympus BH-2 polarizing microscope at crossed and parallel polars (light and polarized light) was used to obtain optical micrographs.…”
Section: Optical Microscopy (Om)mentioning
confidence: 99%
“…The change of cutting temperature was required because all samples were too soft and viscous to be cut at room temperature without deformation. The low temperature cutting preserved the sample morphology (17). An Olympus BH-2 polarizing microscope at crossed and parallel polars (light and polarized light) was used to obtain optical micrographs.…”
Section: Optical Microscopy (Om)mentioning
confidence: 99%
“…The blending of polyethylene with polypropylene has received considerable attention as they are two of the most commonly used thermoplastics. The reason is not only a favorable price/performance ratio, but also the versatility of these materials and very broad range of their possible modification [1–4].…”
Section: Introductionmentioning
confidence: 99%
“…However there have been many studies on PP/EOC blends,13–26 most of the reported works to date employed EOCs have octene content of about 8 mol %. In the present study, we investigate the effect of octene comonomer content in EOC on the morphology and thermal and mechanical properties in PP/EOC blends.…”
Section: Introductionmentioning
confidence: 99%